Integrating Cross-Cultural Religious Literacy and Love-Based Curriculum in Multicultural Social Studies Learning: A Transformative Learning Model for Social Change - Ardillah Abu; Saepudin Mashuri Mashuri; Hasriani Hasriani; Suharto Suharto (Lembaga Bale Literasi, 2026)
The growing complexity of socio-religious challenges in multicultural societies such as identity polarization, digital intolerance, and limited interfaith engagement calls for a transformative approach in Social Studies education. This study aims to develop and examine an integrative learning model based on Cross-Cultural Religious Literacy (CCRL) and the Love-Based Curriculum (LBC) to foster social transformation. Using a qualitative exploratory case study design, this research investigates the implementation of the CCRL-LBC module at Universitas Islam Negeri Datokarama Palu in collaboration with the Leimena Institute. The findings indicate that the model operates through three core competencies personal, comparative, and collaborative-integrated with Panca Cinta values and the Heart-Head-Hand framework. The model is enacted through experiential learning, interfaith dialogue, and community-based collaborative projects. It enhances higher-order thinking skills, cross-cultural religious literacy, empathy, self-awareness, and collaborative capacity across identities. This study highlights the integration of cognitive, affective, and social praxis dimensions within a transformative learning framework. It contributes theoretically to value-based transformative learning and practically offers an innovative model for multicultural Social Studies education, promoting religious moderation, inclusive citizenship, and sustainable social harmony.